2016
DOI: 10.1111/joss.12187
|View full text |Cite
|
Sign up to set email alerts
|

Development of A Lexicon for Commercial Plain Sufu (Fermented Soybean Curd)

Abstract: Sufu (fermented soybean curd) is a cheese‐like product that is widely consumed in Asian countries. One of the subtypes is plain sufu, a traditional fermented food whose sensory attributes remain poorly characterized. In this study, we developed a lexicon for describing its sensory characteristics. Trained panelists evaluated the sensory profiles of 12 commercially available products manufactured in 3 locations. Sensory data were analyzed using one‐way analysis of variance and principal component analysis, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 25 publications
(112 reference statements)
2
56
0
Order By: Relevance
“…The stage of postfermentation positioned fully in the strongly positive PC1 region due to relatively high concentrations of esters, phenols, and alcohols. The results also showed that the categories of flavor elements increased and formed flavoring composition properties throughout the whole ripening period (Chen & Chung, ). Both esters and alcohols were the major classes of compounds, showed the greatest contribution to the whole fermented bean curd flavor profile at the late stage of ripening, and masked the undesirable flavors in the background (Chung, ).…”
Section: Resultsmentioning
confidence: 93%
“…The stage of postfermentation positioned fully in the strongly positive PC1 region due to relatively high concentrations of esters, phenols, and alcohols. The results also showed that the categories of flavor elements increased and formed flavoring composition properties throughout the whole ripening period (Chen & Chung, ). Both esters and alcohols were the major classes of compounds, showed the greatest contribution to the whole fermented bean curd flavor profile at the late stage of ripening, and masked the undesirable flavors in the background (Chung, ).…”
Section: Resultsmentioning
confidence: 93%
“…The recent characteristic taste, umami, recorded highest significant value in the parent species CC and HH than the hybrids (P < 0.05) and this was similar to sweet in the pattern of preferences; probably indicating that sweet contributes to umami. Indeed, the presence of umami taste in products is reportedly triggered by some compounds such as glutamate, a salt of glutamic acid, specific ribonucleotides, and glutamate salts, including monosodium glutamate, potassium glutamate, and calcium glutamate among others (Yamamoto 2003;Meilgarrd et al 2007;Masic and Yeomans 2014;Hajeb and Jinap 2015;Leong et al 2015;Chen and Chung 2016). The basic taste cues of glutamate is its sweetness, therefore, the positive evaluation of umami taste in this study probably indicates the presence of one or more of these compounds that triggered its taste receptors.…”
Section: Fish Samplesmentioning
confidence: 99%
“…For example, this texture lexicon covered all the 19 texture terms described for 50 pasta samples (Irie et al, 2018). Similarly, terms developed in other studies for various products were also included in this lexicon, for example: 4 texture terms to describe 18 different cashew samples (Griffin et al, 2017); 17 out of 20 attributes for 24 French bread samples (Hayakawa, Ukai, Nishida, Kazami, & Kohyama, 2010); 12 out of 14 texture descriptors for 8 commercial red sufu products (He, Chen, & Chung, 2018); all 7 texture attributes for 12 commercial plain sufu products (Chen & Chung, 2016); and 6 of 7 attributes for fresh peaches (Belisle et al, 2017). All 19 texture terms provided for almonds by Civille et al (2010) are included in this texture lexicon.…”
Section: Resultsmentioning
confidence: 99%